Strategy for the treatment of multiple myeloma utilizing monoclonal antibodies: A new era begins. Issue 3 (3rd March 2016) - Magarotto, Valeria; Salvini, Marco; Bonello, Francesca; Bringhen, Sara; Palumbo, Antonio
Abstract: Novel agents, such as immunomodulantory drugs (IMiDs) and proteasome inhibitors (PI), have significantly improved overall survival of multiple myeloma (MM) patients. Yet, MM remains an incurable disease, relapse inevitably occurs and patients tend to become resistant to subsequent treatments. This led to the evaluation of new treatment strategies. The recent development of monoclonal antibodies is changing the treatment algorithm of MM by increasing the therapeutic armamentarium. Elotuzumab and Daratumumab were shown to be very effective and are likely to be soon approved by the FDA. Other antibodies are in pre-clinical or early clinical phases of evaluation and further investigation and more robust data are needed. This review will give an overview of the most active monoclonal antibodies against MM.